Unlocking Potential : Tackling Economic, Institutional and Social Constraints of Informal Entrepreneurship in Sub-Saharan Africa - Grimm, Michael; van der Hoeven, Rolph; Lay, Jann (World Bank, Washington, DC, 2017)
In the past two decades, research on the informal sector has emphasized the heterogeneity of this part of the economy, example in terms of entry costs, firm size, and access to credit, forward- and backward linkages as well as human and physical capital endowments. Yet, not much research has investigated the causes of this heterogeneity and the implied inefficiencies. This is true in particular for Sub-Saharan Africa, where informality dominates urban labor markets. Understanding these causes and the implied inefficiencies is however necessary to design policy interventions that are able to remove the most binding constraints for informal entrepreneurs. This note summarizes the main findings and policy conclusions from a research project that analyzes the quantitative importance of various constraints to informal enterprises in West Africa and Madagascar.